1976
DOI: 10.1002/ar.1091850304
|View full text |Cite
|
Sign up to set email alerts
|

The biosynthesis and secretion of precursor enamel protein by ameloblasts as visualized by autoradiography after tryptophan administration

Abstract: The incorporation of 3H-tryptophan into the inner enamel epithelium of newborn mouse incisor tooth organs has been studied in situ by light and electron microscopic autoradiography to determine the sites and kinetics of biosynthesis, migration, and secretion of precursor enamel protein during newborn mouse incisor tooth formation maxillary and mandibular incisor tooth amelogenesis was studied 5, 30, 60, 120, 240 minutes and 24 hours following the intraperitoneal injection of 3H-tryptophan. By 5 minutes, 40% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1

Year Published

1977
1977
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 45 publications
4
39
1
Order By: Relevance
“…Some authors fixed by immersion in glutaraldehyde or glutaraldehyde-formaldehyde mixture (Garant and Nalbandian, 1968;Matthiessen and Bulow, 1969;Lester, 1970;Katchburian and Holt, 1972;Decker, 1973;Slavkin et al, 1976). Only a few studies used teeth fixed by whole body perfusion (Jessen, 1968;Kallenbach, 1971Kallenbach, , 1973Kallenbach, , 1976Kallenbach, , 1977.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors fixed by immersion in glutaraldehyde or glutaraldehyde-formaldehyde mixture (Garant and Nalbandian, 1968;Matthiessen and Bulow, 1969;Lester, 1970;Katchburian and Holt, 1972;Decker, 1973;Slavkin et al, 1976). Only a few studies used teeth fixed by whole body perfusion (Jessen, 1968;Kallenbach, 1971Kallenbach, , 1973Kallenbach, , 1976Kallenbach, , 1977.…”
Section: Discussionmentioning
confidence: 99%
“…Intact tooth organs were cultured in the presence of [3H]glucosamine (35 ,uCi/,umol; 1 Ci = 3.7 X 1010 becquerels; New England Nuclear) for 24 hr and then chased with 1 mM D-glucosamine for 1 hr. Labeled samples were prepared for autoradiography as described (30).…”
Section: Methodsmentioning
confidence: 99%
“…Sections were incubated at room temperature for 30 min in a humidified chamber with appropriate dilutions of affinity-purified primary;antibody to obtain a final protein concentration of 116 ,ug/ml. After three 10-mi washes with phosphate-buffered saline (pH-7.4), incubation was with a 1:20 dilution of fluorescein isothiocyanate-labeled goat anti-rabbit 7S globulin (Hyland, Costa Mesa, CA) for 30 (4,5,12,14,24,33). In contrast to a recent report by Osman and Ruch (14) (16 ,g); the RF of the band is 0.051.…”
Section: Methodsmentioning
confidence: 99%
“…It has been proposed that the stippled material is a breakdown product resulting from poor fi xation [Nanci and Warshawsky, 1984b]. However, according to Slavkin et al [1976], following the intraperitoneal injection of 3H-tryptophan, the stippled material began to be labeled after 30 min, and labeling was gradually reinforced with time up to 24 h. They concluded that the stippled material represents newly secreted precursor enamel proteins. In addition to these diverging views, it was added by Chen and Eisenmann [1984] that in some experimental conditions, there was no relationship between the formation of stippled material and the fi xative procedure.…”
Section: Possible Differences Between Native Enamel and What Is Obsermentioning
confidence: 99%